Catmagic - Webb, Holly (London, Scholastic, 2008)
The last thing Lottie wants is to spend the holidays with her boring uncle. But when she discovers his pet shop is full of magical animals, everything changes ... There's only one thing that could make Lottie's summer even better- having magical powers of her own.